Diseño de un sistema de explotación para el área de libre aprovechamiento “GADMEP EL GUISME, con código 50001320”, parroquia El Guismi, cantón El Pangui, provincia de Zamora Chinchipe - Herrera Morocho, Valeria Stefania (2023)
The mining activity responsible for the extraction of stony materials since past times have contributed to the development and progress in the implementation of road infrastructure and housing, many concessions of stony material carry out their untechnical extraction, which has generated a waste of resources. The purpose of the free use areas is to grant material for the execution of public works only, these are under the authority of the Municipal GAD, which are in charge of their proper use and control. The present research work was carried out in the free use area GADMEP EL GUISME, with code 50001320, located in El Guismi parish, El Pangui canton, Zamora Chinchipe province, in which the appropriate exploitation method for the study area is Open Sky, once this was determined, we proceeded to analyze proposals for the design of the exploitation system of stone materials, the systems considered were dry graves and graves under water sheet, the first being the system selected. To carry out this purpose, it began with the topographic, bathymetric and geological survey, thus obtaining their maps respectively; the estimation of the reserves through two methods, the method of average height and the method of adjacent cross sections, in which second is the most reliable method. For the implementation of the exploitation system, activities such as, Uncovering, Preparation and Exploitation, were considered, as for the exploitation, the activities were described, such as starting, loading and transport, and the machinery used for these activities and their respective performance Once these activities were determined, the Daily Production was calculated, with this an economic analysis of the free use area was then carried out, and the identification of environmental impacts, through the implementation of the Leopold matrix. Keywords: Free Use, Stone, Exploitation System, Gravel.